Frequency and Correlation of Peripheral and Tissue Eosinophilia With Clinical Manifestations in Patients With Bullous Pemphigoid - Bahareh Abtahi-Naeini; Farhad Zare-Mehrjerdi; Zabihollah Shahmoradi; Fereshte Rastegarnasab; Mojtaba Akbari; Azadeh Zolfaghari; Asiyeh Heidari; Fateme Mohaghegh (Mattioli1885, 2024)
Introduction: Bullous pemphigoid (BP) is an autoimmune disease involving the sub-epidermal layer. Eosinophilia may play a role in the pathogenesis of BP. Objectives: We aimed to investigate the correlation between dermal or peripheral eosinophilia with clinical presentations in patients with BP. Methods: This cross-sectional study was conducted on 108 BP patients from January 2010 to September 2019. Clinical data were recovered. Skin biopsies were re-evaluated, and the Bullous Pemphigoid Disease Area Index (BPDAI) severity score was calculated. Finally, the relationship between clinical features of BP and dermal or peripheral eosinophilia was analyzed. Results: A total number of 108 patients were included in this study. Thirty-five were excluded due to our exclusion criteria. Finally, data from 73 patients were analyzed. 57.5% of the population was female. There was a significant direct correlation (r= 0.33) between BPDAI severity score and tissue eosinophilia (p= 0.03). No significant relationship was found between BPDAI severity score and peripheral eosinophilia (P= 0.52). There were significant positive correlations between tissue eosinophilia with absolute serum eosinophil count (P= 0.002; r= 0.49) and percentage (P< 0.0001; r= 0.89). Conclusion: This study revealed significant relationships between tissue eosinophilia and BP severity. These findings could be useful in clinical practice. The possible role of eosinophils in BP clinical features should be considered as a promising help for better diagnosis and treatment.